The mouse transcription factor‐like 5 gene encodes a protein localized in the manchette and centriole of the elongating spermatid. (27th February 2013) - Shi, Y.; Zhang, L.; Song, S.; Teves, M. E.; Li, H.; Wang, Z.; Hess, R. A.; Jiang, G.; Zhang, Z.
Summary Spermiogenesis is the final phase of spermatogenesis. During this process, haploid round spermatids differentiate into spermatozoa, with dramatic morphological changes, including elongation and condensation of the nuclei, and formation of the flagella. Meig1 is one of many genes involved in the regulation of this process. Male mice deficient in MEIG1 are sterile with a severe defect in spermiogenesis, associated with dramatic disruption of the spermatid manchette and failure of flagellogenesis. A yeast two‐hybrid screen using full‐length MEIG1 as bait identified transcription factor‐like 5 protein (TCFL5) as a putative interacting proteins. Interestingly, this protein was also identified as a potential binding partner of SPAG16, another protein essential for spermatogenesis, and also a binding partner of MEIG1. The interaction between TCFL5 and MEIG1 was confirmed in cultured cells over‐expressing the two proteins. The mouse Tcfl5 transcript is present only in the testis, and its expression is significantly increased during spermiogenesis. However, little is known about TCFL5 protein and its role in male germ cells. A rabbit polyclonal antibody was generated against the C‐terminal region of TCFL5. Mouse TCFL5 protein was expressed in the testis but not in mature spermatozoa. During the first wave of spermatogenesis, TCFL5 expression was dramatically increased at day 30 after birth. In the testis and a mixture of dispersed testicular cells, the protein co‐localized with α‐tubulin, a manchette marker in early elongating spermatids. The protein also localized in the centrioles of late elongating spermatids. No obvious differences in TCFL5 epitope abundance and localization were observed between wild type and the Meig1‐deficient mice. These findings suggest that TCFL5 may play a role upstream of MEIG1 action, and based on putative binding partners and localization is likely to be involved in spermiogenesis and formation of the sperm flagella.